Development of smart application for house condition survey - Afaq Hyder Chohan; Jihad Awad; Chuloh Jung; Adi Irfan Che Ani (Ain Shams Engineering Journal, 2022)
Information based technologies and devices have proven their effectiveness in almost all the aspects of life. In near past it was hard to believe that, building systems and devices can be controlled through phone. However, IT has made it possible and today it is difficulty to think of a normal life without IT. Mobile application is another marvel of IT technology that allows people to carry all essential businesses through various types of mobile applications. Easiness, secure and resourceful are three factors that moves the masses of population to switch overuse of mobile technology. This study has been planned to develop a mobile application to conduct house condition survey. Methodology of study is planned on three core factors i.e. literature review, a data of building defects, and application development process. An inclusive database of low rise building defects (secondary data) was acquired from from earlier research of first author. The acquired secondary data from Chohan, A.H (2007) has surfaced the various types of building defects and their implications in low rise RCC construction/buildings. Data was validated through participation at site and 10 major segments of building defects were identified. Through review of literature research validity was established, application development process was accomplished and various IoT models and similar application were identified. In application development process, study has set the hierarchy of building defects, construed app. development process in domain of building surveying, validate the data, and developed a conceptual plan of smart survey. In addition, defined the development process of mobile application. In section 3, this research has explained the development of mobile application through three major steps i.e. classifying data, setting defects hierarchy and application development. Study has succeeded to surface a prototype framework of smart “Smart Condition Survey” (SCS) which can be practically used for development of real-time mobile application.